Unexpected Social Benefits of Alcoholics Anonymous for Older Women. Issue 1 (April 2016) - Ermann, Lauren S.; Lawson, Gerard; Burge, Penny L.
Abstract : The authors interviewed older women in Alcoholics Anonymous to explore the participants' most beneficial and meaningful experiences in the program. Findings suggested that these women obtained unexpected social benefits from their participation. These benefits are examined through the framework of Carstensen's (1993 ) socioemotional selectivity theory.